Caffeic Acid Inhibits RANKL and TNF-α-induced Phosphorylation of p38 Mitogen-activated Protein Kinase in RAW-D Cells - Ferry Sandra; Ketherin Ketherin (The Prodia Education and Research Institute (PERI), 2018)
BACKGROUND: Caffeic acid inhibits osteoclastogenesis by downregulating expression of Cathepsin K and Nuclear Factor of Activated T cells (NFATc)1, as well as inhibiting activity of Nuclear Factor kB (NFkB). Meanwhile TNF Receptor-associated Factor (TRAF)6 was not influenced by caffeic acid. In order to investigate further caffeic acid's mechanism in inhibiting osteoclastogenesis, regulation of caffeic acid on p38 Mitogen-activated Protein Kinase (MAPK) was investigated.METHODS: RAW-D cells were pretreated with/without caffeic acid and treated with/without 20 ng/mL RANKL and 1 ng/mL TNFα for 0.2, 1, 6, and 12 hour. Tartrate Resistant Acid Phosphatase (TRAP) staining was performed. Then, western blot analysis was performed to detect p38 MAPK and phosphorylated-p38 MAPK. Resulted protein bands were quantified and statistically analyzed.RESULTS: Under induction of 20 ng/mL RANKL and 1 ng/mL TNF-α, RAW-D cells were successfully differentiated into TRAP+ osteoclast-like polynuclear cells. Under treatment of 20 ng/mL of RANKL and 1 ng/mL of TNF-a for 0.2 or 1 hour, significant (p=0,000, T test) increment of phosphorylated p38 MAPK was observed as compared with control. Pretreatment of 10 μg/mL caffeic acid significantly (p=0.000, T test) suppressed the 20 ng/mL of RANKL and 1 ng/mL of TNF-a-induced phosphorylation of p38 MAPK.CONCLUSION: RANKL and TNF-a are potent osteoclastogenesis inductors in RAW-D cells, meanwhile caffeic acid could inhibit the RANKL and TNFa-induced osteoclastogenesis through p38 MAPK.KEYWORDS: caffeic acid, osteoclastogenesis, RANKL, TNF-a, p38, MAPK, RAW-D cells